What can the relation between music and speech show about the brain? A reflection through Patel's "Music, language and the brain" - Kurle, Adriano Bueno (Intuitio, 2015)
In this paper I will try to articulate the relation between speech and music in the mind and brain, using the book “Music, Language and the Brain” by Aniruddh Patel as reference. This piece of work consists of an analysis comparing music and speech in both functions of the brain and cognitive behavior. Patel defends a thesis against the domain-specific theory, and tries to show that it is possible as well as reasonable, using empirical data to show that music and speech have some common ground in the perceiving process. Then it shall be presented three other sources in philosophy, so that we can have other tools to philosophically reason about this matter. I shall briefly present two other perspectives in philosophy: Humean empiricism and Kantian compatibilism. Thus, to contrast with Patel, I shall present Prinz’s empiricist theory, which defends the specific-modality of the senses and perceptions in brain.